Formulasi dan Evaluasi Nutrasetikal Gummy Candy dari Perasan Daun Kelakai (Stenochlaena Palustris (Burm.F.) Bedd): Formulation and Evaluation Nutraceutical Gummy Candy from Kelakai Leaf Juice (Stenochlaena Palustris (Burm.F.) Bedd) - Winiaksa Tri Asdini; Hanggara Arifian; Nur Mita; Rolan Rusli (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Kelakai leaf (Stenochlaena palustris (Burm.F.) Bedd) is a typical plant of East Kalimantan with high iron content which can overcome anemia. The juice of anchovies was formulated into a nutraceutical gummy candy preparation using the Simplex Lattice Design (SLD) method. The results showed that the juice of anise leaves could be used as a gummy candy preparation with an evaluation results that meet the standard with a juice concentration of 9%, pH 5.4, chewy texture, elastic, strawberry essence aroma, sour taste, and brownish yellow color, 11.52% water content, and 2.30% ash content.